Results of treatment with myo-Inositol and D-chiro inositol combination in ratio 5:1 in women with polycystic ovary syndrome - Tatiana A. Oboskalova; Anna V. Vorontsova; Maksim A. Zvychainyi; Karina G. Gushchina; Marietta M. Maitesian (IP Berlin A.V., 2020)
We conducted an observational descriptive study evaluating the effectiveness of therapeutic modification of lifestyle with adding of 1000 mg of myo-inositol and 200 mg of D-chiro inositol combination (ratio 5:1) for nutritional support in 104 women of reproductive age with polycystic ovary syndrome (classic phenotype and nonclassical phenotypes in the presence of hyperandrogenism) for 6 months. Revealed changes in anthropometric parameters (decrease in body mass index by 0.89 kg/m2; p0.05 and waist circumference by 3.0 cm; p0.05), skin status (decrease in the incidence of acne from 96.2 up to 58.6%; p0.05 and seborrhea from 34.6 to 5.8%; p0.05), hormonal profile (statistically significant change in all studied parameters; p0.05: decrease in total testosterone to 1.27 nmol/L and a free androgen index up to 4.12% under an increase in globulin binding sex hormones), carbohydrate metabolism (normalization of glucose tolerance without the development of hypoglycemia) and restoration of menstrual cycle (MC) parameters (regular MC in 76.9 %; p0.05, MC duration 33.4 days; p0.05) indicate a significant role of stage I therapy in patients with polycystic ovary syndrome and the possible benefits of 1000 mg of myo-inositol and 200 mg of D-chiro inositol combination as a nutritional support.